2017
DOI: 10.1080/09513590.2017.1411472
|View full text |Cite
|
Sign up to set email alerts
|

Serum adipokines (adiponectin and resistin) correlation in developing gestational diabetes mellitus: pilot study

Abstract: Adiponectin and resistin are adipose tissue-derived proteins with antagonistic actions; adiponectin has insulin sensitive properties while resistin is involved in the development of insulin resistance. We analyzed adiponectin and resistin levels in gestational diabetes mellitus (GDM) women to evaluate the association of these adipokines in a very high diabetes prevalence population. An age-matched case-control study of GDM and normal pregnant women in Saudi population. We recruited 90 pregnant women at 24-32 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The study of Kuzmicki et al[14] was assigned to the “14-28 wk” subgroup. The studies of Kralisch et al[39], Siddiqui et al[25], and Palik et al[17] were assigned to the subgroup of “after 28 wk”. Additionally, based on the “need for insulin in GDM patients”, the subjects were divided into three subgroups: (1) need for insulin; (2) no need for insulin; and (3) no information.…”
Section: Methodsmentioning
confidence: 99%
“…The study of Kuzmicki et al[14] was assigned to the “14-28 wk” subgroup. The studies of Kralisch et al[39], Siddiqui et al[25], and Palik et al[17] were assigned to the subgroup of “after 28 wk”. Additionally, based on the “need for insulin in GDM patients”, the subjects were divided into three subgroups: (1) need for insulin; (2) no need for insulin; and (3) no information.…”
Section: Methodsmentioning
confidence: 99%
“…Five studies, including two case-control studies, two cohort studies and a prospective observational study with 133, 80, 236, 480 and 196 participants, respectively, as well as one meta-analysis including 11 studies, found no significant difference in resistin levels between GDM and non-GDM pregnant controls [16][17][18][19][20][21]. Four further studies, including two case-control studies with 90, 208, 140 and 130 participants, respectively, observed resistin to be significantly elevated in GDM patients [22][23][24][25], and maternal serum resistin levels were found to correlate positively with the known GDM risk factor LDL cholesterol [22]. Resistin levels in the first and second trimesters were also reported to be positively associated with glycated hemoglobin (HbA1c) in GDM mothers [25].…”
Section: Resistin In Gdm and Pementioning
confidence: 99%
“…This relationship has led us to think that we need to work on this topic with more examples and more comprehensively. Shang et al [ 33 ] showed negative correlation between adiponectin an dresistin levels, while Siddiqui et al [ 34 ] found loweradiponectin and higher resistin levels inwomen with GDM. Guelfi et al [ 35 ] showed decrease inmaternal adiponectin concentrations an increase in leptin and resistin levels with the progression of pregnancy.…”
Section: Discussionmentioning
confidence: 99%